Effect of A Booklet Media on Increasing the Knowledge of Complementary Feeding among Mothers in South Tangerang, Indonesia - Dieta Nurrika; Reni Nofita; Rizka Ardiana Septiyani; Hana Febriyanti; Boy Sabarguna (Journal Of Nursing Practice, 2025)
Background: Nutritional issues among toddlers remain a serious problem in Indonesia. The age of 6–24 months is a critical period in the growth and development of toddlers. Furthermore, children aged 12–23 months were more likely to meet complementary foods (e.g., minimum dietary diversity and minimum acceptable diet) than those younger, indicating that the older the child is, the greater the possibility of them meeting minimum complementary foods. Therefore, understanding complementary foods among mothers is essential for meeting the nutritional needs of children aged 6–11 months. Purpose: To compare mothers' knowledge about complementary foods for children aged 6–11 months in the intervention and control groups in South Tangerang. Methods: This research utilized a quasi-experimental design with a pretest-posttest control group design, carried out between August to September 2022. Participants (n=40) were selected through simple random sampling and then divided into intervention group (n=20) or the control group (n=20). To assess differences in knowledge changes between the two groups, the Wilcoxon signed-rank test was applied in the analysis. Results: The mean scores in the intervention group before and after receiving the booklet were 50.5 and 75.5, respectively. This implies a significant difference between complementary food knowledge mothers in the pre-test and post-test (p-value £0.05). On the other hand, the control group's mean value did not change significantly (pre-test 51.5 and post-test 50.5; p-value >0.05). Conclusion: The present study suggests that the booklet intervention had an impact on increasing mothers' understanding of complementary foods. Thus, health education through booklets is useful in changing knowledge and might be used in posyandu.